Determinación de la prevalencia de la Dipylidiasis canina en perros que llegan a la Clínica Veterinaria Animal House, Babahoyo - Espinoza Indacochea, Rosa Angela (2024)
The experimental research was carried out with the purpose of determining the prevalence of canine Dipylidiasis in dogs treated at the Animal House Veterinary Clinic in Babahoyo, province of Los Ríos. To do this, 30 fecal samples were collected and the flotation technique with supersaturated solution was used to identify the presence of the Dipylidium caninum parasite. Additionally, potential risk factors associated with infection were evaluated, such as age, sex, breed, habitat, presence of fleas, and reported clinical symptoms. The results of the study showed that, of the total number of dogs sampled, only 1 tested positive for Dipylidium caninum, which represents a prevalence of 3.33%. The other 29 dogs were negative, with a prevalence of 96.67%. Finally, no significant differences were found in the risk factors analyzed using the non-parametric Pearson's Chi Square test (χ²), such as age, sex, breed, habitat, presence of fleas, or previous clinical signs and the presence of the disease.